Comparison of two different approaches to hypotension following spinal anaesthesia for Caesarean delivery: effects on neonatal and maternal wellbeing - Zasa, Michele; Conci, Eleonora; Marchignoli, Alessandro; Pini, Rita; Passeri, Lorenzo; Fanelli, Guido; Cornini, Andrea (Acta Biomedica Atenei Parmensis, 2015)
Background: Maternal hypotension during spinal anaesthesia for Caesarean delivery is a common event, with potential detrimental consequences. We led a prospective, randomized study to compare the effects of two strategies on neonatal and maternal wellbeing. Methods: Parturients scheduled for elective Caesarean section in spinal anaesthesia were preoperatively studied with a supine stress test. Those with a positive test were enrolled in the study and received a solution of 0.5% hyperbaric bupivacaine 12.5 mg and 0.02% morphine 200 µg intrathecally. Patients received a 37.5 mg/h preventive intravenous (IV) infusion of ephedrine (Pharmacologic Group), or a 15° left lateral tilt (Non-Pharmacologic Group). In Pharmacolgic Group hypotension was treated for 20% drops in systolic blood pressure; in Non-Pharmacolgic Group only severe hypotension – defined as a 40% drop in systolic blood pressure – was treated. Results: Thirty-six patients were studied. Study groups were statistically similar in terms of demographic variables and intraoperative times. No statistical differences were found in terms of umbilical arterial blood base excess [-1.4 (-3.7 to -0.3) mEq/l Pharmacologic Group vs. -1.7 (-2.7 to -1.0) mEq/l Non-Pharmacologic Group; p=0.815] and other umbilical blood gas values. Apgar scores were statistically similar between study groups. Treatment for hypotension was required by 13 (72.2%) patients in Pharmacologic Group and 9 (50%) patients in Non-Pharmacologic Group (p=0.171). No differences were found at the analysis of serial changes in vital signs. Conclusions: Both studied strategies guaranteed a comparable safe outcome in terms of maternal and neonatal wellbeing. (www.actabiomedica.it)